Studies on Microplastics Morphology Characteristics in the Coastal Water of Makassar City, South Sulawesi, Indonesia - Afdal, Muh.; Werorilang, Shinta; Faizal, Ahmad; Tahir, Akbar (International Journal of Environment, Agriculture and Biotechnology, 2019)
Pollution of plastic waste is the biggest problem in the environment faced by every country, both developing and developed countries. The Continuous entry of plastics into the sea is accompanied by low degradation capabilities that reach tens to hundreds of years and inadequate management of waste making plastic accumulate in the marine environment. Makassar City as one of the big cities in Indonesia, almost 60% of the population spread in the coastal area has the potential to cause pollution of plastic waste distributed through two large rivers, namely the Jeneberang River and Tallo River and city canals and drainage which empties into Makassar City waters. This study aims to identify and quantify microplastic properties on the surface of the water-based on the characteristics of microplastic in Makassar City waters. The method of this research is the survey method using a purposive sampling technique by microscopically analyzing the possibility of microplastic content in seawater samples. Data analysis uses descriptive analysis. The results of the microplastic characteristics found included size and color. Microplastic size classes are grouped into 4 sizes namely: <0.5 mm, 0.5–1 mm, 1.1-2.5 mm and 2.5-5 mm and are dominated by sizes 1.1-2.5 mm (31- 40%), while the microplastic color variations found were 12 colors.